Encyclopedia of Psychopharmacology 2014
DOI: 10.1007/978-3-642-27772-6_66-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Self-Stimulation

Abstract: Rats, and many other vertebrates, will work to deliver electrical pulse trains to certain brain loci via depth electrodes --a phenomenon known as intracranial self--s-mula-on (ICSS). The effect of the electrical sBmulaBon that leads the animal to seek and reiniBate the sBmulaBon is called brain s-mula-on reward (BSR) and is related to the effects of naturally rewarding sBmuli. For example, BSR can compete with, summate with, and subsBtute for, the rewarding effects of natural goal objects such as food and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Second, electrical parameters of stimulation frequency and amplitude were manipulated at single or multiple electrode sites to gain information about the conduction velocity, refractory periods, and connectivity patterns of neurons mediating ICSS (Stellar and Stellar, 1985;Shizgal and Murry, 1989;Yeomans, 1989). These studies implicated low-threshold myelinated neurons as the likely substrate, and these studies also identified multiple parallel networks of neurons capable of supporting ICSS.…”
Section: A Definition Discovery and Neural Substratesmentioning
confidence: 99%
“…Second, electrical parameters of stimulation frequency and amplitude were manipulated at single or multiple electrode sites to gain information about the conduction velocity, refractory periods, and connectivity patterns of neurons mediating ICSS (Stellar and Stellar, 1985;Shizgal and Murry, 1989;Yeomans, 1989). These studies implicated low-threshold myelinated neurons as the likely substrate, and these studies also identified multiple parallel networks of neurons capable of supporting ICSS.…”
Section: A Definition Discovery and Neural Substratesmentioning
confidence: 99%
“…The finding that many species, including humans, will work to receive stimulation of various brain regions has been taken as evidence that those regions encode natural rewards or pleasure 5,6,8,10 . Regions that support ICSS predominantly rest across the medial forebrain bundle, but can also be found in many parts of the limbic and extrapyramidal motor systems 1, [10][11][12][13] . The use of this paradigm for studying the neural substrates of reward has increased considerably in the last decade, afforded in part by the optogenetic revolution that allows for incredibly precise control over neuronal activity in rodents [14][15][16][17][18] .…”
Section: Main Textmentioning
confidence: 99%